Traffic capacity analysis in a one-lane roadwork zone - Skrodenis, Dovydas; Čygas, Donatas; Jakubėnaitė, Ieva (International Conference “Environmental Engineering”, 2020)
Interventions to road are always required to keep road network in a good condition for this reason road works such as maintenance or reconstruction are carried out regularly. Roadwork zone distorts typical driving conditions and brings many unknown factors to driving process that increase the likelihood of an accident or congestion formation. Roadworks zones in Lithuania are a serious problem due to congestion formation, therefore, before the real construction works, it is necessary to carry out traffic flow and capacity modeling as well as to choose the appropriate traffic organization scheme through roadworks zones. The biggest congestion of vehicles in Lithuania occurs in roadworks zones where there is one lane left and traffic is controlled by traffic light, which do not adapt to real traffic conditions, but operate according to the created cycle and frequency model. The simulation analysis of roadwork zone with temporary traffic lights, in order to select optimal green light cycle and frequency is represented, in this paper.
Keywords: roadwork zone; traffic capacity; traffic simulation model; roadwork simulation